Synthesis and Characterization of Aromatic–Aliphatic Polyamide Nanocomposite Films Incorporating a Thermally Stable Organoclay - Zulfiqar Sonia (Nanoscale Research Letters, 2009)
Abstract Nanocomposites were synthesized from reactive thermally stable montmorillonite and aromatic–aliphatic polyamide obtained from 4-aminophenyl sulfone and sebacoyl chloride. Carbonyl chloride terminal chain ends were generated using 1% extra sebacoyl chloride that could interact chemically with the organoclay. The distribution of clay in the nanocomposites was investigated by XRD, SEM, and TEM. Mechanical and thermal properties of these materials were monitored using tensile testing, TGA, and DSC. The results revealed delaminated and intercalated nanostructures leading to improved tensile strength and modulus up to 6 wt% addition of organoclay. The elongation at break and toughness of the nanocomposites decreased with increasing clay contents. The nanocomposites were thermally stable in the range 400–450 °C. The glass transition temperature increased relative to the neat polyamide due to the interfacial interactions between the two phases. Water uptake of the hybrids decreased upon the addition of organoclay depicting reduced permeability.